A case of notomelie observed in a calf - Fahrettin Alkan; Yılmaz Koç; Kamil Beşoluk; Musa Karaman (Eurasian Journal of Veterinary Sciences)
In this case report, notomelie abnormality which was seen in a female and fourty days old cross-breed calf was described. Notomelie in ruminants occur as a result ot exogen and endogen factors or both influences. It may be difficult or in some cases impossible to determine which exerts the greater effect. The notomelie was operated successfully under local anaesthesia and premedication.The case of notomelie is very seldom and interesting on the calves. For this reason, this case has been reported.